Decomposing the education wage gap: Everything but the kitchen sink - Julie L. Hotchkiss; Menbere Shiferaw (Federal Reserve Bank of Atlanta, 2010)
This paper contributes to a large literature concerned with identifying the source of the widening wage gap between high school and college graduates by providing a comprehensive, multidimensional decomposition of wages across both time and educational status. Data from a multitude of sources are brought to bear on the question of the relative importance of labor market supply and demand factors in the determination of those wage differences. The results confirm the importance of investments in and use of technology, which has been the focus of most of the previous literature, but are also able to show that demand and supply factors played very different roles in the growing wage gaps of the 1980s and 1990s.
Keywords: J20; J31; J24; 330; education wage gap; skill wage gap; skill-biased technological change; skill-based wage differentials